Studi Hadis tentang Hakikat, Karakteristik, dan Jenis Materi Pembelajaran dalam Pendidikan Islam - Maslani, Maslani; Muhammad, Mugeni; Fathimah, Nur Sab’rina; Hidayat, Wisnu Hambali (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2025)
This study explores hadiths concerning the essence, characteristics, and types of learning materials in Islamic education. The Prophet Muhammad SAW’s teachings encompass spiritual, intellectual, and social dimensions, intended to shape a holistic individual (al-insan al-kamil). Using a qualitative method, the research analyzes authentic hadiths from primary sources such as Sahih Bukhari, Sahih Muslim, Sunan Tirmidhi, and Sunan Darimi, supported by educational literature. The findings identify three core characteristics of Islamic learning materials: comprehensiveness, moral orientation, and learner-centeredness. These characteristics align with Islamic educational goals that integrate religious and worldly knowledge. The study classifies learning content into five major domains: aqidah (creed), akhlak (morals), ibadah (worship), the Qur’an, and fiqh (Islamic jurisprudence). Each domain is examined through relevant hadiths, with a focus on sanad (chain of narration) and matan (content) validity. The analysis demonstrates how these hadiths can inform the development of curricula that are spiritually grounded yet responsive to contemporary educational challenges. The integration of pedagogical strategies like problem-based learning reinforces the relevance of prophetic teachings in modern contexts. This research underscores the importance of utilizing hadith-based insights to enhance Islamic education and character formation, ensuring the transmission of authentic values across generations.